ผลของยาแก้อักเสบคีโทโรแล็กต่อแอพอปโทซิสและการแสดงออกของยีนซ่อมแซมของเซลล์กระดูกอ่อน - นารีรัตน์ รุ่งเรือง (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Osteoarthritis (OA) is classified in a group of joint diseases. It is caused by the degradation of articular cartilage which stimulates inflammatory responses. Ketorolac is a non-steroidal anti-inflammation drugs (NSAIDs). Nowadays, ketorolac is widely used to treat and relieve pain for OA patients. There is a conception of intra-articular injection of ketorolac. The objective of this research is to study the effects of ketorolac on chondrocyte apoptosis and expression of repair genes. Cartilage samples were obtained from nine OA patients who underwent total knee replacement surgery. Chondrocytes from the articular cartilage samples were cultured and treated with ketorolac at the concentrations of 0, 1, 5, 10 and 20 mg/ml for 24 and 48 hours. Chondrocyte viability was analyzed by MTT assay. Apoptotic cells were detected by TUNEL assay. Dead cells were detected by Live/Dead assay at 24 hours. Expression of the ACAN and BMP2 genes were analyzed by real-time PCR. The chondrocyte viability was significantly decreased after treated with ketorolac at the concentration higher than 1 mg/ml for 24 and 48 hours. TUNEL assay results showed that cells underwent apoptosis in a dose-dependent manner. Live/Dead assay results showed that the cell percent mortality was significantly increased when the chondrocytes were treated with ketorolac at the concentration higher than 1 mg/ml for 24 hours. Furthermore, ketorolac at the concentration of 1 mg/ml significantly decreased the expression of the ACAN gene. Therefore, further study on safety of ketorolac for intra-articular injection is necessary.